2008
DOI: 10.1111/j.1526-4610.2008.00859.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Disability in Migraineurs Referred to a Tertiary Clinic: Neck Pain, Headache Characteristics, and Coping Behaviors

Abstract: These data suggest the need for prospective research exploring the causal mechanisms by which neck pain and coping response influence disability and underscores the importance of multidisciplinary approaches to headache management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
2
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 17 publications
2
44
2
3
Order By: Relevance
“…Avoiding and catastrophizing was not restricted to chronic forms of headache in our study, which is line with many other studies describing such coping behaviour also in episodic headache (Bishop et al, 2001;Ford et al, 2008;Lefebvre et al, 1995;Kolotylo and Broome, 2000;Norton and Asmundson, 2004). Therefore the question arose, whether avoidance behaviour is indeed disadvantageous in migraine?…”
Section: Pain Coping Behavioursupporting
confidence: 92%
See 1 more Smart Citation
“…Avoiding and catastrophizing was not restricted to chronic forms of headache in our study, which is line with many other studies describing such coping behaviour also in episodic headache (Bishop et al, 2001;Ford et al, 2008;Lefebvre et al, 1995;Kolotylo and Broome, 2000;Norton and Asmundson, 2004). Therefore the question arose, whether avoidance behaviour is indeed disadvantageous in migraine?…”
Section: Pain Coping Behavioursupporting
confidence: 92%
“…In headache fear, avoidance anxiety and depression play an important role regarding disability for the individual patient (Hursey and Jacks, 1992;Bishop et al, 2001;Ford et al, 2008;Radat et al, 2008). Predominantly anxiety and depression have been associated with higher levels of stress and functional impact on everyday life.…”
Section: Introductionmentioning
confidence: 99%
“…36 A recent investigation demonstrated that avoidance or disengagement coping (both emotionfocused coping) were associated with headache intensity, vomiting, and nausea. 37 Recent work by Martin and colleagues has indeed challenged the long-held notion that avoiding headache triggers is adaptive, 38 suggesting that avoidance may actually increase sensitivity to triggers in the long term. 39 A related and growing body of literature attests to the benefits of accepting pain, pursuing activities consistent with one's values, and improving functioning/quality of life, especially when elimination of pain is not a realistic goal.…”
Section: Differences In Coping Strategiesmentioning
confidence: 99%
“…In a population study, 94% of persons with migraine reported co-existing TTH [2], and NP was found among 89.3% of persons with migraine with co-existing TTH [3]. The prognosis of migraine may worsen with co-existing TTH [4], and NP has been found to be a predictor of increased disability in persons with migraine [5]. …”
Section: Introductionmentioning
confidence: 99%